2013
DOI: 10.1504/ijicbm.2013.053109
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality and managerial effectiveness among Indian managers

Abstract: Historically, managerial effectiveness is a vital construct, which has been acknowledged by management practitioners in corporate and by researchers in academia. Synchronically, workplace spirituality is another key issue that has been recognised as a valuable concept in the organisational and management context; however, the concept lies in its infancy and neophyte stage, and there is a dearth of empirical studies in this newly developing area. Keeping these views in mind, this study is an attempt to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…In the Indian context, researchers (Chawla and Guda, 2010;Komala and Ganesh, 2007;Pawar, 2009) have done empirical studies and found that in workplaces where spirituality is nurtured, respected and motivated, their employees are more consistent, satisfied and committed and their productivity is high. In a study conducted by Sharma et al (2013) in Punjab (India), OCB was seen as directly related to job satisfaction in Indian public and private sector banks. The researcher has chosen to build on studies of the consequences of workplace spirituality, OCB and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the Indian context, researchers (Chawla and Guda, 2010;Komala and Ganesh, 2007;Pawar, 2009) have done empirical studies and found that in workplaces where spirituality is nurtured, respected and motivated, their employees are more consistent, satisfied and committed and their productivity is high. In a study conducted by Sharma et al (2013) in Punjab (India), OCB was seen as directly related to job satisfaction in Indian public and private sector banks. The researcher has chosen to build on studies of the consequences of workplace spirituality, OCB and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spirituality seems to have systemic interaction with other diversity variables. There is much evidence that the experience and expression of spirituality differs according to diversity aspects such as gender (Briggs and Dixon 2013;Keshet and Simchai 2014;Vosloo, Wissing and Temane 2009) or ethnic and race groups (Archibald 2010;Lewis 2015;Sharma Rastogi and Garg, 2013). In addition, spirituality tends to moderate several outcome behaviors in people from diverse groups (Bliss 2009); Harvey and Martinko 2009;Taylor, Chatters and Jackson 2009), and leads to positive work outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Administrators who value spirituality as a necessary aspect of life reflect the lowest stress, greater humanity, and interconnectedness stakeholder groups and show a huge level of development and innovations (Shinde & Fleck, 2015). The research of (Sharma et al 2013) found that it tends to be recognized as an influencer of administrative effectiveness and efficiency.…”
Section: Spiritualitymentioning
confidence: 99%